Distribution and drift dispersal dynamics of a caddisfly grazer in response to resource abundance and its ontogeny - Katano, Izumi (R Soc Open Sci, 2017)
Stream grazers have a major impact on food web structure and the productivity of stream ecosystems; however, studies on the longitudinal (upstream versus downstream) and temporal changes in their drift dynamics and resulting distributions remain limited. Here, we investigated the longitudinal and temporal distributions and drift propensity of a trichopteran grazer, the caddisfly, Micrasema quadriloba, during its life cycle in a Japanese stream. The distribution of larvae significantly shifted downstream during the fifth instar larval stage during late winter; with periphyton abundance (i.e. their food source) showing similar shifts downstream. Therefore, our results show that the drift dispersal the caddisfly occurs in response to decline in available food resources (i.e. food-resource scarcity) and an increase in food requirements by growing individuals. Furthermore, our results show that this observed longitudinal shift in larval distribution varies through their life cycle, because the drift dispersal of fifth instar larvae was greater than that of immature larvae. The correlation between periphyton abundance and drift propensity of fourth instar larvae was not statistically significant, whereas that of fifth instar larvae was significantly negative. In conclusion, we detected an ontogenetic shift in drift propensity, which might explain the longitudinal and temporal distributions of this species.